Rydberg ions in coherent motional states: a new method for determining the polarizability of Rydberg ions - Niederländer, Marie; Vogel, Jonas; Schulze-Makuch, Alexander; Gély, Bastien; Mokhberi, Arezoo; Schmidt-Kaler, Ferdinand (New Journal of Physics, 2023)
We present a method for measuring the polarizability of Rydberg ions confined in the harmonic potential of a Paul trap. For a highly excited electronic state, the coupling between the electronic wave function and the trapping field modifies the excitation spectra depending on the motional state of the ion. This interaction strongly depends on the polarizability of the excited state and manifests itself in the state-dependent secular frequencies of the ion. We initialize a single trapped 40Ca+ ion from the motional ground state into coherent states with |α| up to 12 using electric voltages on the trap segments. The internal state, firstly initialised in the long-lived 3D_5/2 state, is excited to a Rydberg S_1/2-state via the 5P_3/2 state in a two-photon process. We probe the depletion of the 3D_5/2 state owing to the Rydberg excitation followed by a decay into the internal ground 4S_1/2 state. By analysing the obtained spectra we extract the polarizability of Rydberg states which agree with numerical calculations. The method is applicable to different Rydberg states regardless of their principal or angular quantum numbers. An accurate value of the state polarizability is needed for quantum gate operations with Rydberg ion crystals.<br